Centre for Health Record Linkage: expanding access to linked population data for NSW and the ACT, Australia - Irvine, Katie; Hall, Rick; Taylor, Lee (International Journal of Population Data Science, 2020)
Context The Centre for Health Record Linkage (CHeReL) was established in 2006 as a dedicated health and human services data linkage facility for two Australian jurisdictions, New South Wales and the geographically-nested Australian Capital Territory. The two jurisdictions have their own Governments and separate Health and Human Service systems. Purpose and Operations The primary purpose of the CHeReL is to make linked administrative and routinely collected healthdata available to researchers and government within relevant regulatory and governance frameworks.The CHeReL’s data governance and technical operations draw on international best practice andhave been refined by learnings from other data linkage centres. Outcomes Over twelve years of operation, more than 2,320 unique investigators from 140 institutions haveused the CHeReL, producing 615 publications in peer-reviewed literature. A robust pipeline of newdevelopment is expected to further amplify the use of linked data for cutting edge medical researchand support a vision of data-informed policy and data-driven government services.